Differentiated services enhancements for efficient IP QoS implementation - Abidin, H. Z.; Din, M. N.; Fisal, Norsheila (2005)
To enhance the deployment of DifServ network we propose two mechanisms, i.e. Connection Admission Control (CAC) facility and hierarchical scheduling. In this paper we describe both facilities and report the results of the simulation work. Simulation work was conducted using ns-2. The CAC scheme is parameter-based, where three distinct types of DiffServ traffic were given bandwidth allocation using peak rate, effective rate and mean rate values. In the simulation work, it is found that the admission control scheme gave better service in terms of blocking probability, throughput and queue size compared to normal DiffServ network. Whereas in the hierarchical scheduling scheme, two levels of scheduling were used, i.e. using weighted round robin and priority queuing. The network performance in terms of throughput is observed. The simulation results shows that better performance were achieved with hierarchical scheduling